PENGEMBANGAN BAHAN AJAR MENGGUNAKAN GENIALLY PADA KELAS III MATERI APAKAH SEMUA HEWAN SAMA - Aisya Putri, Nada; Syahiril Anwar, Wawan; Abdul Gani, Resyi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Development of Teaching Materials Using Genially on the Topic 'Are All Animals the Same?' for Third-Grade Students at SDN Ciheuleut 02 Bogor." This research employs the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The study involved 28 third-grade students as the test subjects to develop and evaluate the effectiveness of the interactive teaching materials. The teaching materials were validated by three experts, namely, media experts, language experts, and subject matter experts, yielding highly satisfactory results. The feasibility percentages given were 96% by media experts, 100% by language experts, and 96.2% by subject matter experts, resulting in an overall average of 97.4%, categorized as "Highly Feasible." The trial conducted on the students showed a significant improvement in understanding, with an average score of 91.3%. These results indicate that the interactive teaching materials developed using Genially are highly effective and practical for use in the learning process, and they enhance student engagement and understanding of the topic "Are All Animals the Same?"